Unraveling the Effects of Task Sequencing on the Syntactic Complexity, Accuracy, Lexical Complexity, and Fluency of L2 Written Production - Abdi Tabari, Mahmoud; Miller, Michol (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
Although several studies have explored the effects of task sequencing on second language (L2) production, there is no established set of criteria to sequence tasks for learners in L2 writing classrooms. This study examined the effect of simple ̶ complex task sequencing manipulated along both resource-directing (± number of elements) and resource-dispersing (± planning time) factors on L2 writing compared to individual task performance using Robinson’s (2010) SSARC model of task sequencing. Upper-intermediate L2 learners (N = 90) were randomly divided into two groups: (1) Participants who performed three writing tasks in a simple–complex sequence, and (2) participants who performed either the simple, less complex, or complex task. Findings revealed that simple-complex task sequencing led to increases in syntactic complexity, accuracy, lexical complexity, and fluency, as compared to individual task performance. Results are discussed in light of the SSARC model, and theoretical and pedagogical implications are provided.